INVOLUSI HUTAN RAKYAT (KASUS DI PERBUKITAN MENOREH KABUPATEN KULON PROGO) - , MARIA PALMOLINA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Conditions of poverty that occurs in the farming community and the development of private forests is relatively rapid in Java, provides an overview interesting to see how is strategies that the farmers done where vastland ownership continues to decline, a result of the increasing number of family members in the household farmers. How big change happens, how much minimum land of area required for subsistence farming households, as well as how the farmers responding the limitations of private forest, are the things that will be studied and researched. This study used ethnographic research methods, in order to produce a description of the contents of social culture composed of expressions and behavior of the communities studied. Research sites in the Menoreh Hills in KulonProgo Regency, DIY by reason: (1) The phenomenon of changing patterns of land use from agriculture to private forest. (2) KulonProgo declared as areas that have relatively high poverty rates. The results of this research were occurs involution private forests in the Menoreh hills particular Hargorejo village, with the understanding retardation / stagnation private forest farmers caused by the tendency of the farmers who continually changing landless of the farm into a private forest (50-100% of the land area owned), without followed by knowledge of private forest management, so that the results of the private forests are not different from the results of the farm, and even tended to decline and threaten the food security of their private forest can not be the livelihood of subsistence farming households due to the landless. Land area at least for households private forests at subsistence level seen in the farming community which has a land area > 5000 m2. Strategies of farmers in overcoming the limitations of private forest land to meet subsistence needs is to plant perennials/wood in agricultural land, with the aim to be left to work in the non-agricultural sector (the informal sector).